Black women in post-apartheid South Africa, nation-building and radio: the case of Ukhozi FM - Nkosi, Lethiwe (African Studies, 2014)
Nation-building as it relates to the notion of belonging, is a pertinent topic in post-apartheid South Africa. This is primarily because of the prevailing discourse about nation and belonging in apartheid South Africa, whereby citizenship to large sections of the population was on the basis of skin colour. In its hierarchical definition of citizenship and belonging, black women were on the bottom of the rung. This denial was reinforced through the content that was broadcast on national media. This changed with the advent of constitutional democracy. During the transition period from apartheid, the national media sought to convey messages that portrayed a nation characterised by equality and inclusivity. This minor dissertation is concerned with the extent to which the content broadcast on a radio programme engages black female listeners as citizens. It specifically focuses on the content broadcast on Jabul Ujule (Be Happy and Be Content): a programme on Ukhozi FM. By way of background, it sketches a brief history of how radio was used by both the colonial and apartheid government to 'imagine' South Africa as well as construct a particular kind of public sphere. Following upon this, the dissertation locates Ukhozi FM's history within the continuum that begins with the apartheid era and extends to the post-apartheid period and discusses the station's role during both eras, focusing more fully on the latter period. In short, this minor dissertation looks at the history of Jabul Ujule in terms of the content that was broadcast during the apartheid era in order to understand the way in which black women were and are being engaged in the post-apartheid era. Methodologically, it uses discourse analysis to analyse transcripts of the broadcasts as well as a transcript of an interview with the presenter of the programme. Lastly, this work looks at how the infusion of advertisement into the programme's content limits the extent to which the content engages its female listeners as citizens.